Very high-energy gamma-ray detection and long-term multiwavelength view of the flaring blazar B2 1811+31 - Abe, K.; Abe, S.; Abhir, J.; Abhishek, A.; Acciari, V. A.; Aguasca-Cabot, A.; Agudo, I.; Aniello, T.; Ansoldi, S.; Antonelli, L. A.; Arbet Engels, A.; Arcaro, C.; et al. (EDP Sciences, 2025)
Context. Among the blazars whose emission has been detected up to very high-energy (VHE; 100 GeV<100 TeV) gamma rays, intermediate synchrotron-peaked BL Lacs (IBLs) are quite rare. The IBL B2 1811+31 (z = 0.117) exhibited intense flaring activity in 2020. Detailed characterization of the source emission from radio to gamma-ray energies was achieved with quasi-simultaneous observations, which led to the first-time detection of VHE gamma-ray emission from the source with the MAGIC telescopes.
Aims. In this work, we present a comprehensive multiwavelength (MWL) view of B2 1811+31, with a specific focus on the 2020 VHE flare, employing data from MAGIC, Fermi-LAT, Swift-XRT, Swift-UVOT, and several optical and radio ground-based telescopes.
Methods. Long-term MWL data were employed to contextualize the high-state episode within the source emissions over 18 years. We investigated the variability, cross-correlations, and classification of the source emissions during low and high states. We propose an interpretative leptonic model for the observed radiative high state.
Results. During the 2020 flaring state, the synchrotron peak frequency shifted to higher values and reached the limit of the IBL classification. Variability in timescales of a few hours in the high-energy (HE; 100 MeV<100 GeV) gamma-ray band poses an upper limit of 6x10(14) delta(D) cm on the size of the emission region responsible for the gamma-ray flare, with delta(D) being the relativistic Doppler factor of the region. During the 2020 high state, the average spectrum became harder in the HE gamma-ray band compared to the low states. A similar behavior has been observed in X-rays. Conversely, during different activity periods, we find harder-when-brighter trends in X-rays and a hint of softer-when-brighter trends at HE gamma rays. A long-term HE gamma-ray and optical correlation indicates that the same emission regions dominate the radiative output in both ranges, whereas the evolution at 15 GHz shows no correlation with the fluxes at higher frequencies. We test one-zone and two-zone synchrotron-self-Compton models for describing the broadband spectral energy distribution during the 2020 flaring state and investigate the self-consistency of the proposed scenario.